Bosworth 1485 : a battlefield rediscovered - Foard, Glenn, 1953-; Curry, Anne (Oxbow Books, 2013)
Bosworth stands alongside Naseby and Hastings as one of the three most iconic battles ever fought on English soil. The action on 22 August 1485 brought to an end the dynastic struggle known as the Wars of the Roses and heralded the dawn of the Tudor dynasty. However, Bosworth was also the most famous lost battlefield in England. Between 2005 and 2010, the techniques of battlefield archaeology were used in a major research programme to locate the site. Bosworth 1485: a battlefield rediscovered is the result. Using data from historical documents, landscape archaeology, metal detecting survey, ba.